THE EFFECT OF RESISTANCE BAND EXERCISE ON ACTIVITIES OF DAILY LIVING AND FUNCTIONAL INDEPENDENCE AMONG OLDER ADULTS: A SYSTEMATIC LITERATURE REVIEW - Zakaria, Zaidah; Mat, Samsiah; Alias, Zahariah; Saharin, Amizah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This systematic literature review (SLR) investigates the impact of resistance band exercises on improving physical strength, mobility, and functional independence in older adults. The growing need for effective interventions to promote the health of aging populations has led to the increasing popularity of resistance band exercises due to their low cost, accessibility, and adaptability for individuals with varying physical capabilities. The review synthesizes studies examining the physical and psychosocial benefits of these exercises, particularly for older adults aged 60 and above. It explores the effectiveness of resistance band exercises in improving activities of daily living (ADLs), mobility, balance, and strength, as well as their positive impact on mental health and social engagement. Findings suggest that resistance band exercises offer comparable, if not superior, benefits to more traditional forms of resistance training, such as free weights, especially for individuals with mobility limitations. Additionally, these exercises contribute to improved mood, reduced anxiety, and increased social interaction, which are essential for enhancing overall well-being and combating isolation. Despite the promising results, the review identifies several gaps in the literature, including the need for long-term studies, subgroup-specific research, and further exploration of the physiological mechanisms behind the observed benefits. The review concludes that resistance band exercises are a practical and effective intervention for improving both the physical and psychosocial health of older adults, with significant implications for health practitioners and policymakers.